2015
DOI: 10.1155/2015/680191
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole Associated Neutropenia in a Preterm Neonate Treated for Hyperthyroidism

Abstract: Maternal Graves' disease is relatively uncommon with an estimated incidence of 0.4%–1% of all pregnancies, but only 1–5% of newborns delivered to mothers with Graves' disease develop overt clinical signs and symptoms of hyperthyroidism. Here, we describe a case of a 1380-gram female neonate who was born at 30-week gestation to a mother with Graves' disease. Our patient presented with hyperthyroidism followed by transient hypothyroidism requiring treatment with levothyroxine. While hyperthyroid, she was treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Less commonly, hyperthyroidism is (initially) treated with repeated doses of iodide instead of ATDs. 18,[69][70][71] In extremely ill newborns requiring admission to a NICU for respiratory or cardiac support, a short course of glucocorticoids, which inhibit thyroid hormone secretion and impair peripheral deiodination of T4 to T3, may be necessary.…”
Section: Question 6: What Clinical Indications Should Prompt Initiatimentioning
confidence: 99%
See 2 more Smart Citations
“…Less commonly, hyperthyroidism is (initially) treated with repeated doses of iodide instead of ATDs. 18,[69][70][71] In extremely ill newborns requiring admission to a NICU for respiratory or cardiac support, a short course of glucocorticoids, which inhibit thyroid hormone secretion and impair peripheral deiodination of T4 to T3, may be necessary.…”
Section: Question 6: What Clinical Indications Should Prompt Initiatimentioning
confidence: 99%
“…To the best of our knowledge, only a single case report described the development of neutropenia in a preterm (GA 30 weeks) neonate treated with MMI who recovered after decreasing the dose. 71 Prematurity is not a contraindication to ATD use. However, in 1 study, 2 extremely preterm newborns (GA 25 weeks) demonstrated an unusually rapid (within 48 hours) decrease in fT4 levels after starting carbimazole, indicating that is important to monitor TFTs more closely in preterm newborns.…”
Section: Question 6: What Clinical Indications Should Prompt Initiatimentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the cut-off point of severe neutropenia associated with antithyroid therapy is not defined, however in adults it is usually to be defined as ANC<500 cell/ ul associated with clinical manifestations like fever, sore throat and oral ulcers (5). Our case had bilateral parotitis, fever, sore throat and one oral ulcer associated with decreasing neutropenic count and reached an ANC nadir level of 431 cell/ ul.…”
Section: Case Reportmentioning
confidence: 77%